2010
DOI: 10.1111/j.1462-5822.2010.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-encoded Hsp40 proteins define novel mobile structures in the cytosol of the P. falciparum-infected erythrocyte

Abstract: SummaryPlasmodium falciparum is predicted to transport over 300 proteins to the cytosol of its chosen host cell, the mature human erythrocyte, including 19 members of the Hsp40 family. Here, we have generated transfectant lines expressing GFP-or HA-Strep-tagged versions of these proteins, and used these to investigate both localization and other properties of these Hsp40 co-chaperones. These fusion proteins labelled punctate structures within the infected erythrocyte, initially suggestive of a Maurer's clefts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(182 citation statements)
references
References 72 publications
7
175
0
Order By: Relevance
“…57 It was suggested J-dots could be protein-cholesterol aggregates or vesicular structures of an unusual lipid composition. 30 This may explain absence of a visible membrane in our EM studies around vesicular structures we observed. PfPTP1 and SBP1 occur on these structures and it has been shown that PfEMP1 is found on structures with very similar characteristics.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…57 It was suggested J-dots could be protein-cholesterol aggregates or vesicular structures of an unusual lipid composition. 30 This may explain absence of a visible membrane in our EM studies around vesicular structures we observed. PfPTP1 and SBP1 occur on these structures and it has been shown that PfEMP1 is found on structures with very similar characteristics.…”
Section: Discussionmentioning
confidence: 51%
“…[24][25][26] There are a number of different vesicles described in P falciparum including electron dense vesicles (EDVs), J-dots, and vesicle-like structures (VLSs), which could play a role in PfEMP1 trafficking. [27][28][29][30][31] We have characterized a novel PEXEL-containing protein that we have named P falciparum PfEMP1 trafficking protein.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these exported PfHsp40 proteins were found to be associated with 701 cholesterol containing membranes [121]. They seem to be localized in punctuate, 702 highly mobile structures, termed J-dots.…”
Section: Membrane Modification/protein Export 649mentioning
confidence: 99%
“…Additionaly, there is no known vesicular transport to the Maurer's clefts because none of the vesicles observed could be labeled with antibodies against any Maurer's clefts protein (21,36). Whether these proteins travel via a nontypical vesicular transport or as soluble chaperoned protein complexes (76,81,114) remains to be shown, and recently described J-dots carrying parasitederived HSP40 and HSP70 proteins might play a role in this process (49,50).…”
Section: Proteins Reach Maurer's Clefts Via a Complex Transport Pathwaymentioning
confidence: 99%
“…Only a few proteins are known to be trafficked to structures in the host cell without passing through the Maurer's cleft hub. These proteins include MAHRP2 at tether-like structures (48), heat shock protein 40 (HSP40) and HSP70-x in or at J-dots (49,50), and some soluble proteins in the cytosol, such as ring exported protein 3 (REX3) (40). Although most resident proteins are encoded by single-copy genes, such as membrane associated histidine rich protein 1 (MAHRP1) (41) or knob associated histidine rich protein (KAHRP) (38, 51), Maurer's clefts gain their importance as sorting stations of a number of exported protein families.…”
Section: Maurer's Cleft As Sorting Stationsmentioning
confidence: 99%